The Neuropsychological And Psychosocial Predictors Of Juvenile Delinquency: Comparing Detained Delinquents And Matched Control Group - Turkson, S.M.A. (University of Ghana, 2022)
ABSTRACT The causes of juvenile delinquency are varied. Research has focused largely on psychosocial factors although there is growing evidence that brain factors are equally implicated. Identifying the causes of delinquency is very important as it helps with rehabilitation of youth who are caught in the world of crime or at risk of becoming delinquent. In the present study, the objectives were to investigate broadly, psychological and social predictors of delinquency. Specifically, the objectives were to examine the extent to which selected neurocognitive abilities and psychosocial characteristics can predict delinquency. A battery of neuropsychological tests was used to collect data from 84 detained delinquents and 31 matched controls between the ages of 14 and 18 years. Using the logistic regression analysis, results indicated that poor verbal ability was a robust neuropsychological predictor of juvenile detention. In addition, low socioeconomic status more than doubled the likelihood of juvenile detention. Somatic complaints and rule breaking behavior were emotional/behavioral problems that almost doubled the likelihood of juvenile detention. Inadequate parental supervision; low parental education and childhood abuse/trauma may account for the findings. Recommendations include, extensive neuropsychological evaluations need to be included in the legal decision-making process at the juvenile courts. Prison officers should be trained on the care and management of children with neuropsychological deficits. Teachers should be trained to identify children who are at risk for delinquency, so that early interventions can be made.
MPhil. Clinical Psychology
Keywords: Neuropsychological; Psychosocial Predictors; Juvenile Delinquency; Control Group